La derogación del delito de calumnias del Coip y la inclusión de su conducta en el daño moral con una sanción puramente pecuniaria - Quirola Ochoa, Milton Franklin (2017)
The paper develops arguments for the decriminalization of slander and its inclusion in the Moral Damage treated by Civil Law, based on three main arguments, the exercise of the right to freedom of expression as a mechanism to guarantee democratic societies, Criminal sanctions have an inhibiting effect on citizens, resulting in indirect censorship; third, abuse of criminal law to deal with slander.